PENENTUAN ZONA BAHAYA TSUNAMI BERDASARKAN PEMODELAN DI WILAYAH GUNUNG KIDUL, YOGYAKARTA - Rahayu Robiana; Pandu Adiminarno; Arianne Pingkan L. (PPSDM Geominerba, 2018)
The coast of Gunung Kidul is divided into two type of beaches, straight beaches with cliffs and sloping beaches with bays. Even though the sloping beach is a small part of Gunung Kidul region, but there are high intensity of activities, such as settlements, fishing, and tourism area. The tsunami inundancy mapping through the modeling for narrow beaches with bays requires detailed topographic data obtained through aerial photography using drone. The source of tsunami generation uses earthquake scenarios from the megathrust zone in southern Java with magnitudes of 7.0, 7.5, 8.5 and 8.7. The modeling results show that tsunami with a maximum height can threaten the facilities and buildings in the coastal area where the reasearch takes place, including Baron, Krakal, and Sadeng beach.